Downregulation of UHRF1 increases tumor malignancy by activating the CXCR4/AKT-JNK/IL-6/Snail signaling axis in hepatocellular carcinoma cells - Ji-Hyun Kim; Jae-Woong Shim; Da-Young Eum; Sung Dae Kim; Si Ho Choi; Kwangmo Yang; Kyu Heo; Moon-Taek Park (Scientific Reports, 2017)
Abstract UHRF1 (ubiquitin-like, with PHD and RING finger domains 1) plays a crucial role in DNA methylation, chromatin remodeling and gene expression and is aberrantly upregulated in various types of human cancers. However, the precise role of UHRF1 in cancer remains controversial. In this study, we observed that hypoxia-induced downregulation of UHRF1 contributes to the induction of the epithelial-mesenchymal transition (EMT) in hepatocellular carcinoma cells. By negatively modulating UHRF1 expression, we further showed that UHRF1 deficiency in itself is sufficient to increase the migratory and invasive properties of cells via inducing EMT, increasing the tumorigenic capacity of cells and leading to the expansion of cancer stem-like cells. Epigenetic changes caused by UHRF1 deficiency triggered the upregulation of CXCR4, thereby activating AKT and JNK to increase the expression and secretion of IL-6. In addition, IL-6 readily activated the JAK/STAT3/Snail signaling axis, which subsequently contributed to UHRF1 deficiency-induced EMT. Our results collectively demonstrate that UHRF1 deficiency may play a pivotal role in the malignant alteration of cancer cells.